Depressed adolescents as young adults – Predictors of suicide attempt and non-suicidal self-injury during an 8-year follow-up - Tuisku, Virpi; Kiviruusu, Olli; Pelkonen, Mirjami; Karlsson, Linnea; Strandholm, Thea; Marttunen, Mauri (Journal of affective disorders, 2014)
Clinically derived follow-up studies examining the predictors of suicide attempts (SA) and non-suicidal self-injury (NSSI) among adolescents are scarce. The aims were to study SA and NSSI as predictors of future NSSI and SA, and to study the role of other risk and protective factors, especially alcohol use, and perceived social support from family and peers during a 1-year follow-up and between the 1-year and 8-year follow-ups among consecutively referred depressed adolescent outpatients. The Adolescent Depression Study (ADS) is a longitudinal study of depressed adolescent outpatients (mean age at baseline 16.5 years, 81.8% females). The subjects of the present study (n=139, 63.8% of the original study population) were assessed at baseline, at 1-year and 8-year follow-ups using semi-structured diagnostic interviews (K-SADS-PL) for DSM-IV diagnoses, and structured self-report scales for clinical risk factors. In multivariate comparisons, SAs were predicted both in the 1-year follow-up and in the period between the 1- and 8-year follow-ups by alcohol use and low perceived peer support. NSSI in the 1-year of follow-up was predicted by baseline NSSI, younger age and alcohol use, whereas the only significant predictor for NSSI between the 1- and 8-year follow-ups was NSSI. A large majority of the sample were females, limiting the possibility to analyze gender differences. Among depressed outpatients NSSI is a strong predictor of suicidal behavior, and other factors beyond depression, such as alcohol use and availability of social support, must also be addressed to prevent the recurrence of suicidal behavior.